Some aspects of the toxic effects of cadmium on organism of experimental animals - Khopta, N. S.; Bazalytska, I. S.; Ersteniuk, A. M. (Journal of Education, Health and Sport, 2017)
The work investigates peculiarities of metabolic processes, bioelemental composition and structural changes in white rats’ bone tissue in the presence of cadmium ions (1/10 LD50 CdCl2) damage both singly and in combination. Administration of cadmium ions in male rats has been found to cause the development of dysmicroelementosis accompanied by the disturbance of metabolic processes in bone tissue. It has been observed the disturbance of phosphorous-calcium metabolism in terms of level of different forms of calcium, phosphates, acid and alkaline phosphatase in the dynamics of intoxication development. It has been investigated the content of osteotropic elements and bone tissue mineral density, collagen matrix damage degree by hydroxyproline level and histological examinations. Changes in parathormone and calcitonin levels have been detected. This comprehensive study showed that the most severe disturbances occur on the 14th day after ten-day period of animals’ intoxication with CdCl2.